Political Parties and Public Policy in the German Länder - Turner, E. author. aut Link
VIII, 263 p.
Keywords: Political Parties and Public Policy in the German Länder considers the extent to which, and in what circumstances, political parties affect public policy. Exploring the regional level in Germany; using case studies in the areas of education, childcare and family, and labour market policy.